Association of factor V Leiden G1691A and prothrombin gene G20210A mutations with adverse pregnancy outcomes - Sidra Asad Ali; Bushra Moiz; Lumaan Sheikh (Journal of the Pakistan Medical Association, 2021)
Objective: To determine the association of Factor V Leiden / prothrombin gene mutation in Pakistani women with adverse pregnancy outcomes. Method: The prospective study was conducted at the Aga Khan University Hospital, Karachi, from January 1 to December 31, 2016, and comprised females ?40 years having history of two or more foetal losses with no apparent aetiology. Restriction fragment length polymorphism- Polymerase chain reaction was performed using MnlI and HindIII restriction enzymes for factor V Leiden G1691A and prothrombin gene mutation G20210A. Females with two or more consecutive normal pregnancies were enrolled as the control group. Data was analysed using SPSS 19. Results: Of the 172 participants with a mean age of 29.3±5.9 years (range: 19-38 years). 86(50%) each were healthy controls and those with recurrent pregnancy loss. There were 238 livebirths among the controls compared to 13 in the other group. Factor V Leiden G1691A was identified in 2(2.3%) women, and prothrombin gene mutation G20210A in 1(1.2%) woman in the patient group, while no mutation was identified in the control group. Conclusion: The prevalence of Factor V Leiden / prothrombin gene mutation in women with recurrent pregnancy loss was found to be very low. Continuous....